2006
DOI: 10.1136/pgmj.2005.034512
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for development of venous thromboembolism in Indian patients undergoing major orthopaedic surgery: results of a prospective study

Abstract: The study reconfirms the belief that DVT has a lower incidence in Indian patients as compared with other ethnic groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
71
3
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(98 citation statements)
references
References 52 publications
(22 reference statements)
22
71
3
2
Order By: Relevance
“…3,5,[15][16][17] Studies in Pakistan to asses the frequency of DVT in high-risk surgical patients without thromboprophylaxis revealed an incidence ranging from 0 to 12.8%. 6,18,19 Similarly, studies conducted in neighboring India to asses the risk of DVT in patients undergoing hip and knee arthroplasties reported the incidence of DVT to be 6.1% (Bagaria et al 4 ) and 2.8% ( Jain et al 20 ), respectively, which is significantly lower than the incidence in the West. 8,9 In our study, DVT was found to be more common in patients who had complete SCI and were immobilized for a longer period of time than the patients having incomplete injury or no neurological deficit and who were mobilized earlier.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…3,5,[15][16][17] Studies in Pakistan to asses the frequency of DVT in high-risk surgical patients without thromboprophylaxis revealed an incidence ranging from 0 to 12.8%. 6,18,19 Similarly, studies conducted in neighboring India to asses the risk of DVT in patients undergoing hip and knee arthroplasties reported the incidence of DVT to be 6.1% (Bagaria et al 4 ) and 2.8% ( Jain et al 20 ), respectively, which is significantly lower than the incidence in the West. 8,9 In our study, DVT was found to be more common in patients who had complete SCI and were immobilized for a longer period of time than the patients having incomplete injury or no neurological deficit and who were mobilized earlier.…”
Section: Discussionmentioning
confidence: 98%
“…14 Patients with an SCI are traditionally felt to be at a high risk for developing DVT. 4,6,15 The importance of DVT is in the possibility of pulmonary embolism, which may prove fatal, and chronic venous insufficiency in the long term.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations